Characteristics of ALD‐ZnO Thin Film Transistor Using H2O and H2O2 as Oxygen Sources. Issue 15 (10th April 2022) - Yang, Jun; Bahrami, Amin; Ding, Xingwei; Lehmann, Sebastian; Kruse, Nadine; He, Shiyang; Wang, Bowen; Hantusch, Martin; Nielsch, Kornelius
Abstract: ZnO thin films are deposited by atomic layer deposition (ALD) using diethylzinc as the Zn source and H2 O and H2 O2 as oxygen sources. The oxidant‐ and temperature‐dependent electrical properties and growth characteristics are systematically investigated. Materials analysis results suggest that H2 O2 provides an oxygen‐rich environment so that the oxygen vacancies ( V O ) is suppressed, implying a lower carrier concentration and a higher resistivity. The lower growth rate makes it possible for the ZnO thin films to grow along the lower surface energy direction of <002>, leading to a lower Hall mobility. Furthermore, the ZnO semiconductor is integrated into thin film transistor (TFT) devices and the electrical properties are analyzed. The TFT with H2 O2 ‐ZnO grown at 150 °C shows good electrical properties, such as a high field‐effect mobility of 10.7 cm 2  V –1  s –1, a high ratio I on / I off of 2 × 10 7, a sharp subthreshold swing of 0.25 V dec –1, and a low trapping state ( N trap ) of 2.77 × 10 12  eV –1  cm –2, which provides a new pathway to optimize the performance of metal‐oxide electronics. Abstract : During atomic layer deposition (ALD) ZnO process, H2 O2 provides an oxygen‐rich environment inducing less oxygen vacancies into the ZnO thin film. After applying bias stress of 10 V for 3600 s, the threshold voltage shift for H2 O2 ‐ZnO thin film transistor is only 0.13 V.